Students’ Evaluation of Teaching and Their Academic Achievement in a Higher Education Institution of Ecuador - Sánchez, Tarquino; Gilar-Corbi, Raquel; Castejón, Juan-Luis; Vidal, Jack; León, Jaime (Frontiers in Psychology, 2020)
This paper addresses the relationship between student evaluation of teaching (SET) and academic achievement in higher education. Meta-analytic studies on teaching effectiveness show a wide range of results, ranging from small to medium correlations between SET and student achievement, based on diverse methodological approaches, sample size studies, and contexts. This work aimed to relate SET, prior academic achievement, and academic achievement in a large sample of higher education students and teachers, using different methodological procedures, which consider as distinct units of analysis the group-class and the individuals, the variability between students within classes, and the variability between group-class means, simultaneously. The data analysis included the calculation of group-class means and its relationship with the group-class mean academic achievement, through correlation and hierarchical regression techniques; additionally, a multilevel path analysis was applied to the relationship between prior academic achievement, SET, and their academic achievement, considering the variability among group-class. A multisection analysis was also carried out in those course disciplines in which there was more than one class group (section). The results of individual and group-class analysis revealed that SET was moderately low but related to academic achievement in a significant way once the effect of previous academic achievement was controlled. In addition, multilevel path analysis revealed the effect of SET on achievement, both within and between group-class levels. The results of the analysis carried out in the course disciplines with different sections, according to a multisection design, yielded similar results to the individual and aggregated data analysis. Taken together, the results revealed that SET was low related to academic achievement, once the effect of previous academic achievement was controlled. From these results it follows that the use of SET as a measure of teachers ’effectiveness for making administrative decisions remains controversial.